2021
DOI: 10.3389/fphar.2021.714892
|View full text |Cite
|
Sign up to set email alerts
|

Qiangjing Tablets Regulate Apoptosis and Oxidative Stress via Keap/Nrf2 Pathway to Improve the Reproductive Function in Asthenospermia Rats

Abstract: Asthenozoospermia (AZS), is a common cause of male infertility. Currently, most drugs for azoospermia lack desirable therapeutic efficiency, therefore developing new drug therapy is important. Qiangjing tablets could enhance renal function and improve sperm quality. The purpose of this study was to examine whether Qiangjing tablets could improve the reproductive function in azoospermia rats through activating the Nrf2/ARE pathway, and how to regulate energy metabolism and oxidative stress in this process. Sper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Transcription factor Nrf-2 is an crucial regulator for a variety of cell biological processes, especially oxidative stress [ 52 ], which can modulate the expression of antioxidant enzymes and conjugation/detoxification enzymes, such as HO-1 and NQO-1 [ 53 ]. It has been revealed that both HO-1 and NQO-1 can neutralize the oxidative stress through enhancing the removal of ROS [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transcription factor Nrf-2 is an crucial regulator for a variety of cell biological processes, especially oxidative stress [ 52 ], which can modulate the expression of antioxidant enzymes and conjugation/detoxification enzymes, such as HO-1 and NQO-1 [ 53 ]. It has been revealed that both HO-1 and NQO-1 can neutralize the oxidative stress through enhancing the removal of ROS [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to provide a reliable method for the quality control of QJT, fingerprints of QJT and reference solution were compared in our previous study. At the same chromatographic conditions, there were 12 common peaks in fingerprints of both QJT and reference solution, which showed that the type or content of QJT appeared to no change greatly before and after preparation [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…QJP may improve the quality of sperm in asthenospermic rats by inhibiting apoptosis and oxidative stress. In our previous study, QJP was shown to inhibit the expression of ERK1/2 and vimentin in an SD rat model of asthenospermia, improve sperm quality by inhibiting oxidative stress, 20 reduce the testis expression of the apoptotic factor FasL, 20 inhibit the inflammatory cytokines IL‐1β and TNF‐ɑ in UU‐infected Sertoli cells, 21 and upregulate the expression of the key proteins ZO‐1, occludin and F‐actin in the BTB in cyclophosphamide‐treated rats 22 . These findings indicate that QJP may have the ability to reduce male infertility induced by pollution.…”
Section: Introductionmentioning
confidence: 93%